2012
DOI: 10.1016/j.pbi.2012.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic responses to stress: triple defense?

Abstract: Highlights► Epigenetic control is involved in stress signaling and stress responses. ► Stress can modify epigenetic regulation at many different levels. ► Epigenetic and genetic components of stress responses are connected. ► Epigenetic diversity might be an important factor in stress adaptation and evolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
82
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(86 citation statements)
references
References 63 publications
0
82
0
1
Order By: Relevance
“…Changes in DNA methylation, several posttranslational histone modifications, as well as a linker histone H1 variant have been implicated in plant responses to osmotic/salt stress (2,3,6,10,20,21,(42)(43)(44)(45), but in most cases the relationship among chromatin status, transcriptional responsiveness, and physiological outcomes is not clearly understood. Interestingly, in both metazoans and plants, histone phosphorylation appears to be involved in responses to osmotic/salt stress (3,17,(19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Changes in DNA methylation, several posttranslational histone modifications, as well as a linker histone H1 variant have been implicated in plant responses to osmotic/salt stress (2,3,6,10,20,21,(42)(43)(44)(45), but in most cases the relationship among chromatin status, transcriptional responsiveness, and physiological outcomes is not clearly understood. Interestingly, in both metazoans and plants, histone phosphorylation appears to be involved in responses to osmotic/salt stress (3,17,(19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
“…epigenetics | heterochromatin | histone phosphorylation | abiotic stress | protein kinase P lants, due to their sessile nature, adopt special strategies to cope with adverse environmental conditions, resulting in complex interactions among signaling pathways and developmental programs that impinge on chromatin organization and transcriptional activity (1)(2)(3). A growing body of evidence indicates that changes in DNA methylation and certain posttranslational histone modifications are involved in plant responses to environmental stresses, possibly by modulating the expression of stress responsive genes and/or chromosomal structures (1-6).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Environmental challenges such as stress can lead to alterations in gene expression by changes in chromatin structure at responsive genes and/or the biogenesis of small RNAs (for review, see Gutzat and Mittelsten Scheid 2012). For instance, it was shown that abiotic stress can cause the release of transgene silencing and the reactivation of endogenous heterochromatic loci in Arabidopsis (Lang-Mladek et al 2010;Pecinka et al 2010;TittelElmer et al 2010).…”
Section: Epigenetic Stress Responses and Their Potential Inheritancementioning
confidence: 99%
“…Numerous reports supposedly show that stressinduced epigenetic variation can be inherited during several generations (for review, see Boyko and Kovalchuk 2011;Gutzat and Mittelsten Scheid 2012). In stressed Nicotiana tabacum and Arabidopsis plants, as well as in their unstressed progeny, homologous recombination occurs at a higher frequency than in control plants (Molinier et al 2006;Boyko et al 2007Boyko et al , 2010Kathiria et al 2010).…”
Section: Epigenetic Stress Responses and Their Potential Inheritancementioning
confidence: 99%